A trouble shared is a trouble halved: The role of family identification and identification with humankind in well‐being during the COVID‐19 pandemic. (16th June 2021) - Frenzel, Svenja B.; Junker, Nina M.; Avanzi, Lorenzo; Bolatov, Aidos; Haslam, S. Alexander; Häusser, Jan A.; Kark, Ronit; Meyer, Ines; Mojzisch, Andreas; Monzani, Lucas; Reicher, Stephen; Samekin, Adil; et al.
Abstract : The COVID‐19 pandemic has triggered health‐related anxiety in ways that undermine peoples' mental and physical health. Contextual factors such as living in a high‐risk area might further increase the risk of health deterioration. Based on the Social Identity Approach, we argue that social identities can not only be local that are characterized by social interactions, but also be global that are characterized by a symbolic sense of togetherness and that both of these can be a basis for health. In line with these ideas, we tested how identification with one's family and with humankind relates to stress and physical symptoms while experiencing health‐related anxiety and being exposed to contextual risk factors. We tested our assumptions in a representative sample ( N = 974) two‐wave survey study with a 4‐week time lag. The results show that anxiety at Time 1 was positively related to stress and physical symptoms at Time 2. Feeling exposed to risk factors related to lower physical health, but was unrelated to stress. Family identification and identification with humankind were both negatively associated with subsequent stress and family identification was negatively associated with subsequent physical symptoms. These findings suggest that for social identities to be beneficial for mental health, they can be embodied as well as symbolic.